ANALISIS KESESUAIAN PENERAPAN STANDAR AKUNTANSI KEUANGAN SYARIAH UNTUK PEMBIAYAAN MURABAHAH DENGAN PSAK NOMOR 102 PADA LEMBAGA KEUANGAN MIKRO SYARIAH DI ACEH BESAR - Nurlaili Maghfirah; Evi Mutia; Dinaroe Dinaroe (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2020)
This study aims to examine the implementation of Statement of Financial Accounting Standards (PSAK) Number 102 concerning murabahah financing in Sharia Cooperatives in Aceh Besar and determine the suitability of the application of PSAK 102 on murabahah financing in Sharia Cooperatives in Aceh Besar. The population of this research is 6 Sharia Cooperatives in Aceh Besar which are registered at the Office of Cooperatives and Small and Medium Micro Businesses in Aceh Besar District which are still active until now and which apply murabahah financing. The analysis was conducted by comparing the implementation of accounting treatment on murabahah financing transactions with PSAK 102. The results showed that the accounting treatment of sharia cooperatives in Aceh Besar in terms of recognition and measurement was not fully following PSAK 102, while the accounting treatment on the presentation and disclosure side was following PSAK 102.